Chapter Higher Education and Work-Related Learning from Professionalism to Professionality - Striano, Maura (Studies on Adult Learning and Education, 2018)
Within a complex economic, political, and social scenario that requires high-level competencies as well as increasingly active citizenship, the European and international agenda for higher education needs to be renewed and re-articulated according to new goals and priorities. Higher education should offer students the opportunity to develop aptitudes and acquire advanced but flexible competencies and skills that go beyond mere professionalism and instead focus on the development of a sound professionality